Design of 3D printing osteotomy block for foot based on triply periodic minimal surface - Hai-qiong Xie; Hai-tao Xie; Tao Luo; Bai-yin Yang; Dao-qi Gan; Dong-fa Liao; Lin Cui; Lei Song; Mei-ming Xie (Scientific Reports, 2024)
Abstract The ankle joint, which connects the lower limbs and the sole of the foot, is prone to sprain during walking and sports, which leads to ankle arthritis. Supratroleolar osteotomy is an ankle preserving operation for the treatment of ankle arthritis, in which the osteotomy is an important fixing and supporting part. In order to avoid stress shielding effect as much as possible, the osteotomy block is designed as a porous structure. In this study, the osteotomy block was designed based on three-period minimal surface, and the designed structure was manufactured by 3D printing. The mechanical properties of different structures were studied by mechanical test and finite element simulation. In mechanical tests, the Gyroid structure showed a progressive failure mechanism from bottom to bottom, while the Diamond structure showed a shear failure zone at 45° Angle, which was not conducive to energy absorption and was more prone to brittle fracture than the Gyroid structure. Therefore, the Gyroid structure is valuable for further research in the development of porous osteotomy.